2015
DOI: 10.1063/1.4918742
|View full text |Cite
|
Sign up to set email alerts
|

Solid-liquid interfaces of ionic liquid solutions—Interfacial layering and bulk correlations

Abstract: The influence of the polar, aprotic solvent propylene carbonate on the interfacial structure of the ionic liquid (IL) 1-butyl-1-methylpyrrolidinium tris(pentafluoroethyl)trifluorophosphate on sapphire was investigated by high-energy x-ray reflectivity. Experiments at solvent concentrations between 17 mol. % and 83 mol. % bridge the gap between diluted electrolytes described by the classical Gouy-Chapman theory and pure ionic liquids. Analysis of our experimental data revealed interfacial profiles comprised of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
70
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 45 publications
5
70
1
Order By: Relevance
“…This region is characterized by low enough concentrations so that steric effects are perturbative, and the model reduces to the PNP theory of dilute electrolytes (or Poisson-Boltzmann (PB) theory if steady states are of interest). The latter also demonstrates that sufficiently diluted IL, either by solvent 47 or possibly by formation of ion-pairs, 19,50 can behave as dilute electrolytes.…”
Section: Analysis: Non-monotonic Screening Lengthmentioning
confidence: 99%
See 2 more Smart Citations
“…This region is characterized by low enough concentrations so that steric effects are perturbative, and the model reduces to the PNP theory of dilute electrolytes (or Poisson-Boltzmann (PB) theory if steady states are of interest). The latter also demonstrates that sufficiently diluted IL, either by solvent 47 or possibly by formation of ion-pairs, 19,50 can behave as dilute electrolytes.…”
Section: Analysis: Non-monotonic Screening Lengthmentioning
confidence: 99%
“…The insets A-C in Figure 2 present steady-state solutions of (4) with parameters corresponding to the ionic liquid, [C 4 C 1 Pyrr][NTf 2 ], diluted with propylene carbonate (C 4 H 6 O 3 ). Indeed, a transition from layered to monotonic EDL has been observed using high-energy x-ray reflectivity 47 and in situ AFM 48 within the range of parameters considered here. The molecular origin for the transition from monotonic to spatially oscillatory EDL, a.k.a.…”
Section: Analysis: Non-monotonic Screening Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction of overscreening into the theory [8] leads to a complicated set of equations, but its effect on capacitance is tricky: although it broadens somewhat the capacitance curve, alone, without the introduction of the compact layer, it does not substantially reduce the 1 Their existence has also been detected directly by X-ray [6,[45][46][47][48][49] and indirectly by scanning nano-probe techniques [50][51][52][53][54][55][56]. Generally, oscillating profiles and overscreening in dense ionic solutions have a long history.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of Refs. 72-74 studied the effects of short-range correla-2 Experimental verifications of oscillating structures in the double layer of ionic liquids [6,[45][46][47][48][49][50][51][52][53][54][55][56] have all been detected near ideally atomically flat surfaces, and we are not aware of any systematic investigations of how they may be perturbed or eliminated by the atomic roughness of the surface [56]. However, computer simulations have specially studied step-edge defects in carbon electrodes [65,66] and surface roughness on a similar scale to molecular dimensions [5,67], which have demonstrated that the resonance effect could be damped.…”
Section: Introductionmentioning
confidence: 99%